The development of E-dictionary for the use with "maharat al-Qiraah" textbook at a Matriculation Centre in a University in Malaysia - Che Omar, Che Abdul Majid; Awang Mat Dahan, Hassan Basri (Sakarya University, Turkey, 2011)
This is an action research to develop an E-Dictionary for the use with Maharah al-Qiraah (Reading skills) textbook at a matriculation centre. The research attempts to answer four research questions: a) What is the database model for an electronic dictionary using Microsoft Access for the use with Maharah al-Qiraah textbook? b) What are the features of a user-friendly electronic dictionary? c) How suitable is an E-Dictionary for the use with Maharah al-Qiraah textbook? and; d) Is E-Dictionary suitable and easy to use? Two types of instrument are used for the research: the E-Dictionary itself and two sets of evaluation form filled by three experienced Arabic teachers and 3 computer experts. The data obtained from questionnaires are analysed using Statistical Package for Social Science (SPSS) version 11.0 to obtain the mean of the evaluation form. The results of the study indicate that an electronic dictionary model using Microsoft Access is valid and suitable. Presenting electronic dictionary in a CD-ROM with an attractive screen is the major feature of a user-friendly electronic dictionary. E-Dictionary is also valid in terms of the Maharah al-Qiraah textbook content and it is convenient to use. The findings of this study is hoped to provide information on the development of Arabic electronic dictionary.